Analisis Geographically Weighted Regression (GWR) Berbasis Pemetaan pada Jumlah Menara Telepon Seluler di Kabupaten Lombok Tengah Tahun 2021 - Wati, Rana Ambarwati; Febiana, Izu Izatul; Hastuti, Siti Hariati (Department of Mathematics, Universitas Negeri Gorontalo, 2025)
Cell towers are tall structures where telecommunications equipment and antennas are installed to support cellular networks. This research aims to analyze the influence of Population Size (X1) and the Number of Service Operators (X2) on the Number of Cellular Phone Towers (Y ) in 139 villages in Central Lombok Regency in 2021. The Geographically Weighted Regression (GWR) method is used to understand spatial variability in the relationship between variables (X1) and (X2) with respect to variable Y . This method is an advancement of the OLS regression analysis method, taking spatial variability into account. By using this method, it is hoped that more accurate spatial distribution patterns can be identified, along with solutions that can assist in the planning of telecommunications infrastructure development in this area. The analysis results indicate that there is significant spatial variability in the distribution of the number of cellular towers based on the Breusch-Pagan test. The significance test results for the parameters show that only the Population Size variable (X1) has a significant effect on the Number of Cellular Towers (Y ) across all observation units (villages) in Central Lombok Regency. The comparison of models shows that the GWR model for the Number of Cellular Towers is better than the OLS Regression, with lower AIC and SSE values and a higher coefficient of determination (R2).